Lung function and radiographic change in chrysotile workers in Swaziland. Issue 4 (November 1982) - McDermott, M; Bevan, M M; Elmes, P C; Allardice, J T; Bradley, A C
Abstract : The effect on lung function and radiographic indices of exposure to chrysotile asbestos was investigated by cross-sectional studies in two groups of men at Havelock Mine, Swaziland. The first group consisted of 214 employees and ex-employees, mean age 52, who had been employed for at least 10 years, and whose dust exposure ranged from minimal for surface workers to very heavy for those in the grading and bagging sections of the mill. In this group 29% had category 1 or more simple pneumoconiosis and 4.5% category 2 or more. For surface and mine workers, the estimated annual deterioration in FEV1 and FVC and the increase in category of pneumoconiosis was similar to that due to age alone, while the heaviest exposure almost doubled the decline in lung function and trebled the rate of progression of pneumoconiosis. The second group consisted of 224 men, mean age 33, all currently working in the mill and having been employed there for at least a year. In this group 30% had category 1 or more simple pneumoconiosis, and 2.7% category 2. Exposure in the dustiest sections of the mill more than doubled the estimated annual decline in lung function and doubled the rate of progression of pneumoconiosis.